Enhancing electrocatalytic water splitting by strain engineering - You, Bo (2020)
Electrochemical water splitting driven by sustainable energy such as solar, wind, and tide is attracting ever-increasing attention for sustainable production of clean hydrogen fuel from water. Leveraging these advances requires efficient and earth-abundant electrocatalysts to accelerate the kinetically sluggish hydrogen and oxygen evolution reactions (HER and OER). A large number of advanced water-splitting electrocatalysts have been developed through recent understanding of the electrochemical nature and engineering approaches. Specifically, strain engineering offers a novel route to promote the electrocatalytic HER/OER performances for efficient water splitting. Herein, the recent theoretical and experimental progress on applying strain to enhance heterogeneous electrocatalysts for both HER and OER are reviewed and future opportunities are discussed. A brief introduction of the fundamentals of water-splitting reactions, and the rationalization for utilizing mechanical strain to tune an electrocatalyst is given, followed by a discussion of the recent advances on strain-promoted HER and OER, with special emphasis given to combined theoretical and experimental approaches for determining the optimal straining effect for water electrolysis, along with experimental approaches for creating and characterizing strain in nanocatalysts, particularly emerging 2D nanomaterials. Finally, a vision for a future sustainable hydrogen fuel community based on strain-promoted water electrolysis is proposed.